Sustainable multifunctional biochar-based cementitious composites for carbon sequestration, energy storage, and smart infrastructure applications: A review - Hilal Khan; Zamil Bin Zahid; Fazal Hussain; Junaid Ahmad; Rao Arsalan Khushnood (Case Studies in Construction Materials)
The decarbonization of construction materials requires multifunctional systems that simultaneously deliver mechanical performance, environmental benefit, and smart functionalities. This review presents a comprehensive analysis of biochar-based cementitious composites as bio-based, carbon-negative materials that unify structural enhancement, carbon sequestration, and supercapacitance behavior. This comprehensive review examines biochar-based cementitious composites as promising bio-based, carbon-negative materials that integrate structural enhancement, carbon sequestration, and smart functionalities. The review covers biochar's impact on flow properties, hydration kinetics, mechanical characteristics, durability performance, and smart functionalities including self-sensing, electromagnetic interference shielding, and energy storage capabilities. Microstructural analyses using advanced characterization techniques reveal the mechanisms underlying biochar's effects on cement matrix development. The sustainability assessment encompasses life cycle analysis and techno-economic evaluation, while stakeholder perspectives has also been discussed to provide insights into adoption potential. This review identifies critical research gaps and provides strategic recommendations for future development. These findings position biochar cementitious composite as a multifunctional, carbon-negative platform for circular, smart infrastructure, bridging materials science, sustainability, and real-world applicability in the built environment.